Multiallergen-specific immunotherapy in polysensitized patients: where are we?. (February 2013) - Bahceciler, Nerin Nadir; Galip, Nilufer; Cobanoglu, Nazan
Allergen-specific immunotherapy administered by the subcutaneous route was introduced a century ago and has been shown to be effective in the management of allergic rhinitis and asthma. More recently, the sublingual administration of allergen extracts has become popular, especially in European countries, and has also demonstrated efficacy in respiratory allergic diseases. Both modes of allergen administration during immunotherapy have been shown not only to reduce symptoms and the need for medication, but also to prevent the development of additional sensitivities in monosensitized patients, as well as asthma development in patients with allergic rhinitis, with a long-lasting effect after the completion of several years of treatment. Almost all of the well-designed and double-blinded, placebo-controlled studies evaluated treatment with single-allergen extracts. Therefore, most meta-analyses published to date evaluated immunotherapy with single allergen or extracts containing several cross-reactive allergens. As a result, in general, multiallergen immunotherapy in polysensitized patients (mixture of noncross-reactive allergens) is not recommended owing to lack of evidence. Although some guidelines have recommended against the use of multiallergen mixtures, allergists commonly use mixtures to which the patient is sensitive with the rationale that effective immunotherapy should include all major sensitivities. Literature on this subject is scarce in spite of the widespread use worldwide. Here, this issue will be extensively discussed based on currently available literature and future perspectives will also be explored.